An analysis of death euphemisms in sarawak malay community from the perspective of cognitive semantics [Analisis eufemisme kematian masyarakat melayu sarawak dari perspektif semantik kognitif] - Wahab, Hamidah Abdul; Ho Abdullah, Imran Ho; Mis, Mohammed Azlan; Salehuddin, Khazriyati (Universiti Kebangsaan Malaysia Press, 2016)
This paper investigates the cognitive processes underlying death euphemisms used by the Sarawak Malay community. These euphemisms are polite forms of language used to replace those that are considered harsh or taboo, and inappropriate for direct speech. Through the use of death-related euphemisms, speakers are able to demonstrate politeness, thoughtfulness and awareness of others’ feelings. This study, which adopts the perspective of cognitive semantics, uses the Conceptual Metaphor theoretical framework proposed by Lakoff and Johnson (1980). Several cognitive mechanisms were used to analyse the data such as image schema and conceptual metaphor. The data was collected through interviews, recordings and observations involving informants who were Malay speakers from Kuching, Sarawak. The analysis reveals that the conceptualisation of death euphemisms in Sarawak Malay speakers is based on the source-path-goal image schema, in addition to the conceptual metaphor DEATH IS A BETTER LOCATION, LIFE IS A JOURNEY, and DEATH IS A DEPARTURE [DEATH IS A JOURNEY]. In general, this study shows that the Malay culture and Islam have largely influenced the conceptualisation of death euphemisms in the Sarawak Malay community. This influence is observable through the use of soft expressions to show courtesy, in keeping with the Malay culture, which emphasizes politeness in communication. The reality of death for Muslims who will return to their Creator, Allah s.w.t., is also depicted in the euphemisms investigated. This linguistic study may serve as a reference for readers and researchers on the topic of Sarawak Malay euphemism, particularly in the field of cognitive semantics